Information techniques of deep machine learning for the analysis of land cover changes - Kussul, N. N.; Shelestov, A.Yu.; Lavreniuk, M. S.; Butko, I. N. (Reports of the National Academy of Sciences of Ukraine, 2016)
The paper proposes a method and an information technique for the geospatial analysis of land cover changes from long-term satellite observations. Since it is a big data problem, we propose a deep machine learning method for its solution, which is based on a hierarchical neural network model. The method allows solving the wide range of applied problems of the analysis of land cover changes and land use.